Business strategies and annual report readability. (11th July 2018) - Habib, Ahsan; Hasan, Mostafa Monzur
Abstract: This study investigates the association between firm‐level business strategy and the readability of narrative disclosures in annual reports. As business strategy affects the information environment and financial performance of firms, we expect the readability of narrative disclosures to vary with the particular business strategy that a firm pursues. In accord with this expectation, we find that firms with prospector‐type business strategies produce less readable narratives, while those with defender‐type business strategies produce more readable narratives. We also document that the association between strategy and readability is partially mediated by organisational performance, although the mediation effect is rather modest. These findings are robust when subjected to a series of sensitivity tests.